PERAN PEMERINTAH DESA DALAM PENGEMBANGAN DESA WISATA DI DESA MASALILI KECAMATAN KONTUNAGA KABUPATEN MUNA - Julada, Wa Ode; Sifatu, Wa Ode; Alim, Abdul (Universitas Halu Oleo, 2021)
This study aims to describe and analyze the role of government and society in the development of tourist villages in Masalili Village, Kontunaga District, Muna Regency. The theory used to read the data is the theory of Economic, Social and Cultural Capital (The Forms of Capital) Pierre Bourdieu (1986). The method used is a qualitative descriptive method, which is obtained through observation, interviews and documentation on matters relating to the role of government and society in the development of tourist villages in Masalili Village. The results of the research on the role of the government in the development of the Masalili tourist village in terms of economic capital are seen in the use of village funds as the main capital in the development of the Masalili peak tourist attraction. In addition, in terms of social capital, it can be seen from the cooperative relationship between the village government and the district government as well as investors such as Bank Indonesia, by providing assistance in the form of facilities and infrastructure for the development of the Masalili tourist village in the future. Meanwhile, in terms of cultural capital, the village government participates in expressing creative ideas for the development of the Masalili tourist village through the availability of spots that can increase the attractiveness of tourists to visit the tourist village. Furthermore, an analysis of the community's role in the development of the Masalili tourism village can be seen from the cultural capital and social capital which includes cooperation between communities in terms of preserving the Muna weaving which is the icon of the tourist village. Meanwhile, in terms of cultural capital provided by the community in the form of creating unique design motifs in each weaving produced and also creating new creations in the form of accessories that can be used as souvenirs for tourists. The conclusion is that the role of the government and the community is very influential in the development of the Masalili tourism village. This can be seen by the combination of capital owned by the government and the community to support the sustainable development of the Masalili tourism village.Keywords: Tourism Village, Capital, Masalili Village.